KNOWLEDGE MANAGEMENT TO IMPROVE TEACHER’S PERFORMANCE: A SYSTEMATIC LITERATURE REVIEW - Martiarini, Elyza; Candra, Eva Nurul (IdeBahasa, 2025)
Knowledge management is an activity carried out by teachers in educational institutions to organise, share, and implement knowledge so that it can be utilised for institutional advancement. This activity includes identifying, developing, sharing, applying, and disseminating knowledge. The aim of this research is to review on how teachers’ knowledge management practices contribute to individual performance and school development. The research employed a Systematic Literature Review (SLR) with a qualitative descriptive design and was carried out systematically by applying PRISMA's guidelines for analysing and summarising systematic reviews. On the basis systematic search of Google Scholar database, there were 45 articles were eligible and 6 articles were included. The review also highlights that the discussion of knowledge management in education draws on several theoretical fields, including knowledge creation theory (Nonaka & Takeuchi). The findings indicate and consistently show that effective knowledge management enhances teachers’ capacity to innovate, collaborate, and adapt to change, which in turn strengthens teaching strategies, professional competence, and overall work performance.